Understanding smallholder irrigation in Sub-Saharan Africa: results of a sample survey from nine countries - Shah, Tushaar; Verma, Shilp; Pavelic, Paul (2023)
Smallholder irrigation is emerging as a development priority in Sub-Saharan Africa. Based on a survey of 1554 smallholders from nine countries, this paper compares rainfed farming with gravity-flow, manual-lift and motor-pump irrigation. Motor-pump-irrigation farmers reported the highest net value added per acre and per family worker, with gravity-flow and manual-irrigation farmers earning marginally more than rainfed-only farmers. In addition to making affordable pumps more readily available, improving the availability of working capital, enhancing security of tenure and ensuring the availability of affordable fuel are all likely to accelerate smallholder irrigation development in Sub-Saharan Africa.